2000
DOI: 10.1109/23.856495
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal and isochronal annealing experiments on irradiated commercial power VDMOSFETs

Abstract: The paper presents results of a study of post-irradiation effects in two types of gamma-ray iiradiated power VDMOSFETs, commercially available from different manufacturers. Isothermal annealing with constant and switching gate bias, as well as isochronal annealing have been performed. The application of charge-pumping measurements in commercial three-teiminal VDMOSFETs is also discussed. Besides enabling insight into the post-irradiation response of investigated devices, obtained results point out some interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…2 was measured some 20 h after the switch; however, it takes only several minutes, if not even less, for dramatic changes in ⌬N ot to occur. 10 These changes are shown to be reversible: switching the bias to positive again leads to ⌬N ot values close to the values before the first bias switch. 10 It can be concluded that during phase 2 of annealing, the oxide-trap charge is not permanently neutralized, but rather temporarily compensated by the electrons tunneling from Si under the positive bias.…”
Section: ͓S0003-6951͑01͒02601-8͔mentioning
confidence: 99%
See 2 more Smart Citations
“…2 was measured some 20 h after the switch; however, it takes only several minutes, if not even less, for dramatic changes in ⌬N ot to occur. 10 These changes are shown to be reversible: switching the bias to positive again leads to ⌬N ot values close to the values before the first bias switch. 10 It can be concluded that during phase 2 of annealing, the oxide-trap charge is not permanently neutralized, but rather temporarily compensated by the electrons tunneling from Si under the positive bias.…”
Section: ͓S0003-6951͑01͒02601-8͔mentioning
confidence: 99%
“…10 These changes are shown to be reversible: switching the bias to positive again leads to ⌬N ot values close to the values before the first bias switch. 10 It can be concluded that during phase 2 of annealing, the oxide-trap charge is not permanently neutralized, but rather temporarily compensated by the electrons tunneling from Si under the positive bias. 11 When the bias is switched at later annealing times, i.e., at the end of phase 3 ͑140 and 170°C data͒, ⌬N ot also rebounds, but not quite to its preannealing value, while ⌬N it changes are almost negligible.…”
Section: ͓S0003-6951͑01͒02601-8͔mentioning
confidence: 99%
See 1 more Smart Citation